Polymicrobial Infective Endocarditis: Clinical Features and Prognosis. Issue 49 (December 2015) - García-Granja, Pablo Elpidio; López, Javier; Vilacosta, Isidre; Ortiz-Bautista, Carlos; Sevilla, Teresa; Olmos, Carmen; Sarriá, Cristina; Ferrera, Carlos; Gómez, Itziar; Román, José Alberto San
Abstract : Abstract: To describe the profile of left-sided polymicrobial endocarditis (PE) and to compare it with monomicrobial endocarditis (ME). Among 1011 episodes of left-sided endocarditis consecutively diagnosed in 3 tertiary centers, between January 1, 1996 and December 31, 2014, 60 were polymicrobial (5.9%), 821 monomicrobial (81.7%), and in 123 no microorganism was detected (12.2%). Seven patients (0.7%) were excluded from the analysis because contamination of biologic tissue could not be discarded. The authors described the clinical, microbiologic, echocardiographic, and outcome of patients with PE and compared it with ME. Mean age was 64 years SD 16 years, 67% were men and 30% nosocomial. Diabetes mellitus (35%) were the most frequent comorbidities, fever (67%) and heart failure (43%) the most common symptoms at admission. Prosthetic valves (50%) were the most frequent infection location and coagulase-negative Staphylococci (48%) and enterococci (37%) the leading etiologies. The most repeated combination was coagulase-negative Staphylococci with enterococci (n = 9). Polymicrobial endocarditis appeared more frequently in patients with underlying disease (70% versus 56%, P  = 0.036), mostly diabetics (35% versus 24%, P  = 0.044) with previous cardiac surgery (15% versus 8% P  = 0.049) and prosthetic valves (50% versus 37%, P  = 0.038). Coagulase-negative Staphylococci, enterococci, Gram-negative bacilli, anaerobes, and fungi were more frequent in PE. No differences on age, sex, symptoms, need of surgery, and in-hospital mortality were detected. Polymicrobial endocarditis represents 5.9% of episodes of left-sided endocarditis in our series. Despite relevant demographic and microbiologic differences between PE and ME, short-term outcome is similar.